Effects of Continuous Cultivation of Soil on Termites (Isoptera) Diversity and Abundance in Savannas of Northern of Côte d’Ivoire - Ténon, Coulibaly; Jean-Pierre, Boga; Ahoua , YAPI; Philippe, Kouassi Kouassi (Asian Journal of Agriculture and Rural Development, 2013)
To highlight the continuous cultivation of soil on biodiversity in savannas of Korhogo in the north of Côte d’Ivoire, termites were studied with regard to their use as bio-indicators of habitat change in the tropics. Using a standardized method, termites were sampled in five types of plots (PCR 1, PCR 2, PCR 3, PCR 10 and PCR 30) which age of continuous cultivation varies from 1 to 30 years in comparison with the primary savanna. The diversity of termites has differed statistically between the habitat types. The species richness highest in the primary savanna (24 species), decreases progressively with the continuous cultivation of soil to reach lowest in the elderly cultures plots PRC 30 (9 species), either 64 % of reduction. Continuous cultivation of soil causes a drastic reduction in soil-feeders group (75 % of reduction on PCR 2). But there was no significant change in termites’ diversity between the savanna and the recent culture PCR 1. The cultivation of soil would have, in the first years, a positive effect on the diversity and abundance of wood feeders. This study shows the impact inflicted by the continuous cultivation of soil on the communities of termites in Korhogo region.